Safeguarding and Promoting the Welfare of Unaccompanied Asylum Seeking Children and Young People; all Wales Practice Guidance - Tracey Maegusuku-Hewett (Wales Strategic Migration Partnership, 2011)
This guidance, is for professionals working with unaccompanied asylum seeking children. It aims to help professionals from a variety of agencies to understand the complex policy and practice in relation to protecting unaccompanied asylum seeking children and young people in Wales. The guide is underpinned by the principle of child first, migrant second. It also includes the views and experiences of young people gathered during focus groups, these experiences are also summarised as an annex. Areas covered by the guidance include: specific risks, interpretation and communication, advocacy, age assessment process, accommodation and support, health needs, education, asylum claims, pathway planning, and complaints. A multi-agency actions checklist, an actions flowchart and a list of useful resources are also included.